Tinjauan Kritis terhadap Sistem Pemilihan dan Pencalonan Kepala Daerah - Adnan, M. Fachri (Jurnal Demokrasi, 2005)
This article discusses the implementation of direct elections at provincial and district government in Indonesia. There are two weaknesses of these  elections, that is, election system and nomination of candidat. First, candidate who get more than  25 % votes of total votes could win the election, if there is no candidat got more than that. Second, candidate could only be nominated by political parties. It means no ringht for  interest groups, busenessmen, or academisions to nominate the candidate to be elected in proviancial dan district government. To solve those problems, election system and nomination of candidate need to be reviewed. Kata kunci: Sistem Pemilihan,  Kepala Daerah, pencalonan